Analisis Reaksi Pasar Modal pada Sektor Perbankan Terhadap Kebijakan Pemerintah Tentang Penyaluran Dana Rp 200 Triliun (Event Study pada Saham Himbara) - Ana Julita; Fitriaty; Muhammad Haris Saputra (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
This study aims to analyze the reaction of the capital market through abnormal returns and trading volume activity to the announcement of the policy of distributing funds of Rp200 trillion to state-owned banks (HIMBARA) announced by the Minister of Finance of the Republic of Indonesia on September 10, 2025. The research was conducted with a time span for seven consecutive days before, D-day to 7 days after the announcement of the event. This study involved five banks with a total sampling method. The results of the paired t-test The results of the study indicate that there was no significant change in abnormal returns and trading volume activity before and after the announcement of the Rp200 trillion fund disbursement policy.